AN ADAPTIVE IMAGE STEGANOGRAPHY COMPRESSION METHOD BASED ON DWT - Ali, Saleh; Al-khoja, Saif; Tawfeeq, Nabeel (Iraqi Journal of Science, 2024)
Steganography is the art of hiding messages in an unsuspected cover. The aim of this paper is to hide larger number of multi messages inside one cover image depending, using the low-low-block-features LLBF of wavelet transformation. The method of embedding messages based on Least-Significant-Bit (LSB) of cover image. The imperceptibility of the messages and cover images is assessed by using the Mean- Square-Error (MSE), the peak signal to noise ratio (PSNR) and the image histogram.